Fluid-structure interactions. - Paidoussis, M. P. (Academic Press, 1998)
This volume emphasizes the fundamentals and mechanisms giving rise to flow-induced vibration of use to researchers, designers, and operators. Fluid-Structure Interactions provides useful problem-solving tools, and conveys the ideas in a physically comprehensible manner. The book includes a complete bibliography of important work in the field. . The Non-linear behaviour of Fluid-Structure interactions . The possible existence of chaotic oscillations . The use of this area as a model to demonstrate new mathematical techniques This book will prove invaluable to researchers, practitioners, and students in fluid-structure interactions, flow-induced vibrations, and dynamics and vibrations.